Performance analysis of indium antimonide thermophotovoltaic system with varied material and geometrical properties - Mohd Jasni M.S.; Choong J.S.; Wan Abd Rashid W.E.S.; Abdul Wahab Y.; Wan Muhamad Hatta S.F. (Elsevier Ltd, 2023)
Cells; Cytology; Electronic design automation; Erbium compounds; Gallium arsenide; Geometry; III-V semiconductors; Indium alloys; Indium antimonides; Photoelectrochemical cells; Photovoltaic cells; Semiconducting gallium; Semiconducting indium; Semiconducting indium gallium arsenide; Semiconductor alloys; Different geometry; Generate electricity; Geometrical property; Indium antimonide; Performance; Performances analysis; Surface irradiation; TCAD modeling; Thermophotovoltaic systems; Thermophotovoltaics; Efficiency